2013
DOI: 10.1055/s-0032-1321799
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Muscle Adaptation to Electrical Stimulation

Abstract: The aims were to investigate the plasticity of the myosin heavy chain (MHC) phenotype following neuromuscular electrical stimulation (NMES) and to assess the correlation between MHC isoform distribution and muscle fibre conduction velocity (MFCV).14 men were subjected to 24 sessions of quadriceps NMES. Needle biopsies were taken from the dominant vastus lateralis and neuromuscular tests were performed on the dominant thigh before and after training. NMES significantly increased the quadriceps maximal force by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The new quantification procedure described here could possibly be combined with the simultaneous examination of other tissue properties. Such additional properties could include muscle fiber type composition, different cytokines, and gene expression (Maffulli et al, 2011;Minetto et al, 2013;Heinemeier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The new quantification procedure described here could possibly be combined with the simultaneous examination of other tissue properties. Such additional properties could include muscle fiber type composition, different cytokines, and gene expression (Maffulli et al, 2011;Minetto et al, 2013;Heinemeier et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting, however, that whereas many types of standard physical exercise can be difficult to implement in the context of hypoxic procedures or when osteoarticular conditions are present, ME is easier to apply and has been shown to be efficient in reproducing training effects [27,28]. That said, muscle adaptations to electro-stimulation could be different [40], and although normobaric and hypobaric hypoxia are similar, they can provoke different physiological responses [41,42]. …”
Section: Discussionmentioning
confidence: 99%
“…After finding no correlations between conduction velocity and the relative content of MHC isoforms in the quadriceps muscle, Minetto et al (2013) (Minetto et al, 2013). The study by Minetto and colleagues supports the claims made by Farina (2008); Minetto et al 2013described that proportions of fiber types and training-induced changes could not be estimated from conduction velocity; they did not find differences between conduction velocity estimates obtained at 70% mean voluntary contraction (when primarily type II fibers should be active) and…”
Section: Noninvasive Measurements Of Physiologic Changementioning
confidence: 71%
“…Kupa et al (1995) demonstrated that fast-twitch (glycolytic) fibers of muscles in rat specimens had greater initial values of MF and conduction velocity and greater change of these variables over time. However, the study by Minetto et al (2013) suggested that conduction velocity could not estimate different fiber types. Furthermore, the points made by Farina (2008) exemplifies why conduction velocity would not be an adequate variable alone to suggest changes related to muscle fiber types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation